School Textbooks and the Study of Industrial Geography in Lower Secondary Education in Romania. - Viorel PARASCHIV; Cristina-Georgiana VOICU; Gheorghi NICULIȚA (Romanian Review of Geographical Education)
The first part of the article outlines the place of industry in Romania’s official curriculum, starting with early education, continuing through primary education in subjects such as Mathematics and Environmental Exploration, Science, and Geography, and ending with secondary school Geography. The second part of this article suggests learning activities aimed at raising students’ awareness of errors in 8th-grade geography textbooks and developing both transversal skills (researching, analyzing, interpreting, and evaluating data, as well as investigating) and geography-specific competencies.